2017
DOI: 10.1097/md.0000000000006886
|View full text |Cite
|
Sign up to set email alerts
|

Quick outpatient diagnosis in small district or general tertiary hospitals

Abstract: While quick diagnosis units (QDUs) have expanded as an innovative cost-effective alternative to admission for workup, studies investigating how QDUs compare are lacking. This study aimed to comparatively describe the diagnostic performance of the QDU of an urban district hospital and the QDU of its reference general hospital.This was an observational descriptive study of 336 consecutive outpatients aged ≥18 years referred to the QDU of a urban district hospital in Barcelona (QDU1) during 2009 to 2016 for evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The variables recorded were the same as reported elsewhere. [ 12 ] The information on the number and dates of the appointments at the QDU and the diagnostic tests as well as the reason for referral and the final diagnosis were obtained from the hospital electronic clinical records. The referral reason was dichotomized into clinical or paraclinical features suggestive of malignancy vs other referral reasons (see supplementary material) for statistical analyses purposes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables recorded were the same as reported elsewhere. [ 12 ] The information on the number and dates of the appointments at the QDU and the diagnostic tests as well as the reason for referral and the final diagnosis were obtained from the hospital electronic clinical records. The referral reason was dichotomized into clinical or paraclinical features suggestive of malignancy vs other referral reasons (see supplementary material) for statistical analyses purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last 15 years several QDUs have been set up in Catalonia as a mean of reaching diagnoses rapidly and without the problems and costs related to hospitalization [ 10 ] . There are QDUs in almost all types of hospitals, from university (like Hospital Clínic de Barcelona) [ 11 ] to small district ones (like Hospital Plató) [ 12 ] . Despite the spread of these QDUs, the available evidence on their activity and the predictors of their time-to-diagnosis and cost outcomes is scanty, particularly in the case of nonuniversity, nontertiary centers.…”
Section: Introductionmentioning
confidence: 99%
“…The structure, indications for referral, and operating procedures of these units have been reported previously [6,10,14,15]. Briefly, they work as ambulatory clinics evaluating patients with suspected severe disorders whose general physical condition is acceptable enough to enable them to go to hospital for investigations and appointments, then back to home.…”
Section: Settingsmentioning
confidence: 99%
“…The unit is open 5 days a week [11,12]. In contrast, the unit of the secondary hospital is staffed with two part-time general internists as well as administrative personnel [10,15].…”
Section: Settingsmentioning
confidence: 99%
“…Different, mainly observational studies revealed that these units were as clinically effective as inpatient admission to reach a diagnosis, with similar diagnostic times. While patient reported satisfaction was also similar or higher than conventional hospitalization, quick diagnosis units proved cost-effective with associated costs significantly lower than the same costs applied to the evaluation of the same conditions in the hospital setting [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%